Intracellular pH in the OK cell. I. Identification of H+ conductance and observations on buffering capacity - Graber, M; DiPaola, J; Hsiang, F L; Barry, C; Pastoriza, E (The American journal of physiology, 1991)
The regulation of intracellular pH (pHi) in the opossum kidney (OK) cell line was studied in vitro using the pH-sensitive excitation ratio of 2',7'-bis(2-carboxyethyl)-5(6)-carboxyfluorescein. Recovery from an NH4Cl acid load disclosed a Na-dependent component blocked by amiloride and a smaller Na-independent component. The Na-independent recovery rate was proportional to the H+ gradient from cell to buffer and was zero in the absence of an electrochemical gradient. The Na-independent recovery was not affected by N-ethylmaleimide, dicyclohexylcarbodiimide, HCO3, phloretin, or ZnCl2 but was accelerated in depolarized cells and by membrane-fluidizing drugs and was inhibited by glutaraldehyde. The apparent cellular buffering capacity changed in proportion to this H+ conductance. Consistent with an electrogenic H+ leak, steady-state cell pH alkalinized with depolarization and acidified with hyperpolarization. Removal of buffer Na+ produced a profound acidification, as did amiloride. In 0-Na+ buffers, extremely large cell-to-buffer H+ gradients were present and proportional to buffer pH. 4-Acetamido-4'-isothiocyanostilbene-2,2'-disulfonic acid and 4,4'-diisothiocyanostilbene-2,2'-disulfonic acid had no effect on steady-state pHi. Measurements of intracellular buffering capacity were derived from the change of cell pH induced by withdrawing NH4Cl. This buffering capacity was increased threefold in Na-free buffers, whereas the value measured by direct titration of cell lysate was the same or less than that of control cells. The NH4Cl-derived buffering capacity varied in direct proportion to the magnitude of the H+ leak. Drugs that changed H+ permeability produced the apparent changes of the measured buffering capacity within a few minutes. We conclude that, in HCO3-free buffer, the OK cell uses two membrane acid-base transport pathways: a Na-H antiporter active at physiological pH and a substantial passive H+ conductance. The results also reveal that the NH4Cl-derived buffering capacity is subject to artifacts, possibly due to a finite leak of ionic NH4+.